Bleaney-Bowersova enačba za opis magnetizma bakrovih dimerov - Kebrič, Matjaž (Matrika, 2018)
In this paper the Bleaney-Bowers equation for copper dimers is examined. First a short introduction is made by describing the diamagnetic and paramagnetic ordering of magnetic moments. Orbital quenching is also described. Description of copper dimers and the derivation of the Bleaney-Bowers equation from the Heisenberg model of interaction between two half integer spins follows. In order to make a realistic model, paramagnetic term is added due to possible impurities in the sample and a constant diamagnetic term is added due to the signal from other atoms. Finally the model is tested on experimental data.
Keywords: bakrovi dimeri; copper dimers; fizika trdne snovi; magnetism; magnetizem; orbital quenching; orbitalno senčenje; solid state physics